2021
DOI: 10.1002/mar.21492
|View full text |Cite
|
Sign up to set email alerts
|

Consumers as creative agents: How required effort influences willingness to engage

Abstract: Consumers often engage with brands by participating in activities such as cocreating products and contributing ideas about product promotion. Such engagement enables consumers to be creative agents rather than mere end-users. However, it also places a burden on them, as it inevitably requires effort on the consumer part. This study investigates the impact of expected effort level (low vs. high) on consumers' inclination toward engagement, and its underlying mechanisms.Three experiments find that higher expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
(194 reference statements)
0
4
0
Order By: Relevance
“…Physical energy investment takes on various forms, depending on the field of research. For example, in intervention research, physical energy investment can be captured via attendance, appointment keeping, or adherence to treatment protocols (King et al, 2014), whereas in consumer research, it may involve consumption activities, providing reviews and recommendations, blogging or vlogging, and even cocreating products with companies (Zeng & Mourali, 2021). Across fields, physical energy investment is often labeled as “participation” (King et al, 2014; Mai et al, 2021).…”
Section: Engagement As a Multidimensional Constructmentioning
confidence: 99%
“…Physical energy investment takes on various forms, depending on the field of research. For example, in intervention research, physical energy investment can be captured via attendance, appointment keeping, or adherence to treatment protocols (King et al, 2014), whereas in consumer research, it may involve consumption activities, providing reviews and recommendations, blogging or vlogging, and even cocreating products with companies (Zeng & Mourali, 2021). Across fields, physical energy investment is often labeled as “participation” (King et al, 2014; Mai et al, 2021).…”
Section: Engagement As a Multidimensional Constructmentioning
confidence: 99%
“…We take this multidimensional perspective, as it not only captures SE's observable engagement behavior, but also, its underlying cognitions and emotions (Bissola & Imperatori, 2016), thus offering more comprehensive SE-based insight. For example, while employees will spend time, thought, and effort in engaging with their job (Zeng & Mourali, 2021), suppliers' engagement will see them purchase, move, and (re)distribute stock, while also liaising with their staff and clients, exposing their respective cognitive, emotional, and behavioral engagement.…”
Section: Sementioning
confidence: 99%
“…We take this multidimensional perspective, as it not only captures SE's observable engagement behavior, but also, its underlying cognitions and emotions (Bissola & Imperatori, 2016), thus offering more comprehensive SE‐based insight. For example, while employees will spend time, thought, and effort in engaging with their job (Zeng & Mourali, 2021), suppliers' engagement will see them purchase, move, and (re)distribute stock, while also liaising with their staff and clients, exposing their respective cognitive, emotional, and behavioral engagement. Moreover, in the context of dark triad‐based personality traits, we expect a stakeholder's cognitive, emotional, and behavioral engagement to affect (or be affected by) these traits, as discussed further in Section 3, thus revealing the applicability of a multi (vs. uni)dimensional SE perspective in our analyses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existing literature has repeatedly demonstrated that involving consumers in the customization process is crucial (Zeng & Mourali, 2021). High involvement will increase product satisfaction and identification (Franke & Schreier, 2010; Kwon et al, 2017), brand loyalty (Yoo & Park, 2016), and willingness to pay (Franke et al, 2010; Randall et al, 2007).…”
Section: Introductionmentioning
confidence: 99%